الشعرية وتجلياتها في مدونة العقد الفريد لابن عبد ربه الأندلسي (ت327ه) - بوسعيد محمد (My University, 2021)
تتناول هذه المقاربة حضور الخطاب الشعري في مدونة العقد الفريد لابن عبد ربه الأندلسي، محاولة استكشاف رؤيته لفن الشعر ، وما حوته مدونته من نصوص شعرية تلبي مطالب الأمة الثقافية والروحية والجمالية، باعتبار الشعرالفن الأول الذي نشأ متناغماً مع الذات العربية، ومعبراً عن وعيها وعمق ارتباطها بالحياة،ارتباطاً ينم عن قلق وجودي تراكم عبر التاريخ، وتردد صداه في بنية النص الشعري. Summary this appoach deals with the presence of poetic discurse in"Al Akd Al farid" of Ibn Abd Rabbu al-Andalusi, in order to explore the author's vision to poetry through the verses of his text that respond to the nation needs in cultural, spiritual and aesthetic matters, in regard that poetry is considered as the first art to have grown in harmony with the Arab identity, expressing at the same time its awareness and the .depth of its attachment to life forward his existential anxiety accumulated throughout history reflected in the structure of the poetic.
Keywords: مد ; مدنة- العقد الفريد-الشعرية- الانتقاءالأدبي- نقد النقد- الانزياح